PAIRS TRADING WITH COPULA METHOD - SETIAWAN (10114007), ARIF
Pairs trading is a stock investment strategy. This strategy use two high correlated stocks. High correlation indicates that the two stocks move together and have long- run equilibrium. In this research, we will use copula method to determine when the two stocks deviate from their equilibrium. The proposed method can identify dependence structure between stocks so it can describe the deviation more accurate. Then the simulation using the copula method will be done with several different parameters and the results will be seen.